The relationship between job satisfaction and employee loyalty in the manufacturing industry of China - Shi, He (2014)
The purpose of this study is to examine the relationship between job satisfaction and employee loyalty through research on the factors which influence employee loyalty, and puts forward some strategies to improve staff loyalty. Analysis of personal variables such as gender, age, education, marriage, work time, level and type of work, and income level variables on job satisfaction and employee loyalty difference do exist, and are based on the existing difference for different types of employees to implement targeted retention strategy. This study will be conducted in Chinese manufacturing enterprises, which are located in Mainland China. I select one manufacturing company of my hometown. This company has more than 200 employees. In this study I use 20 employees as example and all of objectives are more 200 employees. Whether the enterprise staff's job satisfaction and turnover rate are high and low produce a very big effect. At the same time, job satisfaction and employee loyalty are positively correlated. In this study, the questionnaire data analysis was by SPSS 13.0 for Windows software package which provides descriptive statistics, reliability and validity analysis, the differences of characteristic variables and individual analysis, correlation analysis, regression analysis and other methods. According to the finding of this study, job satisfaction and employee loyalty are positive correlation, when workers have more satisfaction, they have more loyalty in the company